1990
DOI: 10.1002/ajmg.1320360410
|View full text |Cite
|
Sign up to set email alerts
|

Blood serotonin and tryptophan in Tourette syndrome

Abstract: Blood serotonin and tryptophan levels were studied in 1,440 individuals. These included patients with Tourette syndrome (TS), attention deficit hyperactivity disorder (ADHA), or ADHD with a family history of TS (ADHD 2 degrees TS); relatives (parents, sibs) of these patients; other patients with TS-like disorders; and controls. There were significant decreases in the serotonin/platelet ratio (P = 0.0001) and in tryptophan (P less than 0.0001) in unmedicated patients with TS. Parents of TS patients showed a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 85 publications
1
26
1
1
Order By: Relevance
“…Also, significantly decreased serum tryptophan levels of TS patients have been reported in two large-scale studies, 50,51 which would be compatible with increased turnover of tryptophan along the kynurenine pathway. However, cerebrospinal fluid tryptophan levels were found to be normal in a different study.…”
Section: Altered Tryptophan Metabolism and Data On Cytokinesmentioning
confidence: 78%
“…Also, significantly decreased serum tryptophan levels of TS patients have been reported in two large-scale studies, 50,51 which would be compatible with increased turnover of tryptophan along the kynurenine pathway. However, cerebrospinal fluid tryptophan levels were found to be normal in a different study.…”
Section: Altered Tryptophan Metabolism and Data On Cytokinesmentioning
confidence: 78%
“…However, our study also includes the concomitant 5-HT 2A R measure, indicative of a trend for elevations in 5-HT 2A BP. 5-HT abnormalities have been hypothesized in TS, although there are conflicting reports regarding 5-HT metabolism (Comings, 1990;Leckman et al, 1984). Some abnormalities that have been hypothesized to be related to co-morbidity with OCD include decreased SERT in platelets (Weizman et al, 1992).…”
Section: -Ht and Da Relationshipsmentioning
confidence: 99%
“…A role for serotonin is suggested by a reduction in cerebrospinal fluid of 5-hydroxyindoleacetic acid (Leckman et al, 1995), the principal metabolite of serotonin and by a reduction of plasma tryptophan, whole blood serotonin, and the 24-h urine secretion of serotonin in some patients with TS (Comings, 1990). Moreover, a PET study suggested decreased serotonin transporter (SERT) binding potential (Wong et al, 2008).…”
Section: Neurotransmitter Abnormalities Associated With Tsmentioning
confidence: 99%